No!: The Power of Disagreement in a World that Wants to Get Along - Charlan Nemeth (London Atlantic Books, 2018)
We like to get along, at home or in the workplace. We don't want to hurt people or offend. Therefore, it is no surprise that numerous famous psychological experiments have proven that we don't tend to go against authority or the majority view. Famous management gurus share the view that harmony, cohesiveness and agreement are the building blocks for effective decision-making and creativity. But they are wrong. In No!, Charlan Nemeth, the world's leading expert on dissent, uses her 35 years of research to show why we need rebels - and how fostering more disagreement can dramatically improve decisions and the production of good ideas. Using examples from Twelve Angry Men to brainstorming, she explains how people with minority opinions need the space to express themselves uncompromisingly, even if it causes discomfort. Explaining why the devil's advocate technique doesn't work and why authentic disagreement is necessary to open our perspectives, this book has the power to revolutionise business, creative organisations, and society.